Explosive radiation in high Andean Hypericum—rates of diversification among New World lineages - Nürk, Nicolai M.; Scheriau, Charlotte; Madriñán, Santiago (Frontiers in Genetics, 2013)
The páramos, high-elevation Andean grasslands ranging from ca. 2800 m to the snow line, harbor one of the fastest evolving biomes worldwide since their appearance in the northern Andes 3–5 million years (Ma) ago. Hypericum (St. John’s wort), with over 65% of its Neotropical species, has a center of diversity in these high Mountain ecosystems. Using nuclear rDNA internal transcribed spacer (ITS) sequences of a broad sample of New World Hypericum species we investigate phylogenetic patterns, estimate divergence times, and provide the first insights into diversification rates within the genus in the Neotropics. Two lineages appear to have independently dispersed into South America around 3.5 Ma ago, one of which has radiated in the páramos (Brathys). We find strong support for the polyphyly of section Trigynobrathys, several species of which group within Brathys, while others are found in temperate lowland South America (Trigynobrathys s.str.). All páramo species of Hypericum group in one clade. Within these páramo Hypericum species enormous phenotypic evolution has taken place (life forms from arborescent to prostrate shrubs) evidently in a short time frame. We hypothesize multiple mechanisms to be responsible for the low differentiation in the ITS region contrary to the high morphological diversity found in Hypericum in the páramos. Amongst these may be ongoing hybridization and incomplete lineage sorting, as well as the putative adaptive radiation, which can explain the contrast between phenotypic diversity and the close phylogenetic relationships.